AlluraClarity Radiation Dose–Reduction Technology in the Hybrid Operating Room During Endovascular Aneurysm Repair. (February 2016) - de Ruiter, Quirina M. B.; Moll, Frans L.; Gijsberts, Crystel M.; van Herwaarden, Joost A.
Purpose: To evaluate the effect of radiation dose reduction with the Allura ClarityIQ image processing technology for fixed C-arms in comparison with a mobile C-arm and an Allura fixed C-arm without ClarityIQ technology during endovascular aneurysm repair (EVAR) procedures.Methods: Radiation dose data from 85 patients (mean age 74.2±7.8 years; 68 men) undergoing EVAR with mobile and fixed C-arm fluoroscopy were retrospectively analyzed. The radiation dose parameters included the kerma area product (KAP), fluoroscopic time (FT), and number of digital subtraction angiography (DSA) frames (FrDSA ). KAPtotal consisted of KAPfluoro (KAP for fluoroscopic imaging) and KAPDSA (KAP for DSA and single shots). Linear regression analysis was used to explore differences in the association of KAP with the FT, FrDSA, and body mass index (BMI) among the 3 C-arms.Results: The mean KAPtotal values for mobile, Allura C-arm, and AlluraClarity C-arm for noncomplex EVARs were 56±39, 245±142, and 157±120 Gy·cm 2 (p<0.001); for complex EVARs, the values were 110±43, 874±653, and 598±319 Gy·cm 2 (p<0.001), respectively. On average, KAPfluoro tripled when the mobile C-arm was replaced by the fixed C-arm. There were no significant differences in the KAPfluoro adjusted for the FT between Allura and AlluraClarity (p=0.69). However, there was a major 61% reduction in KAPDSA from 1.36 Gy·cm 2 per DSA frame for Allura to 0.54 Gy·cm 2 per DSA frame with AlluraClarity (p=0.03). For the mobile C-arm, BMI was not associated with KAP (p=0.13). The associations of BMI with KAPfluoro and KAPDSA were significant for both fixed C-arms but were more robust for Allura compared to AlluraClarity (p=0.02 for KAPfluoro and p<0.001 for KAPDSA ).Conclusion: Changing a mobile C-arm for a fixed C-arm in a hybrid operating suite increased the average intraoperative dose during EVAR. Upgrading the Allura fixed C-arm with ClarityIQ technology resulted in a 61% reduction in the radiation per DSA frame.